International financial reform : the broad agenda - Ocampo, José Antonio (ECLAC SantiagoCL, 1999)
Argues that the agenda for international financial reform must be broadened in at least two senses viz. firstly, it should go beyond the issues of financial prevention and resolution, to those associated with development finance for poor and small countries, and to the 'ownership' of economic and development policies by countries; secondly, it should consider in a systematic fashion, not only the role of world institutions but also of regional arrangements and the explicit definition of areas where national autonomy should be maintained.